2020
DOI: 10.1111/jopy.12583
|View full text |Cite
|
Sign up to set email alerts
|

Self‐transcendence and life stories of humanistic growth among late‐midlife adults

Abstract: Objective: Self-transcendence is the experience of feeling connected to something greater than oneself. Previous studies have shown high scores on self-transcendence are associated with wellbeing and other psychological benefits, but have rarely examined the lived experiences of highly self-transcendent people. Method: Black and White men and women in late-midlife completed Life Story Interviews and self-report measures of self-transcendence. In Study 1 (N = 144, Mage = 56.4), we used grounded theory methodolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 75 publications
(128 reference statements)
0
34
0
Order By: Relevance
“…Likewise, Maurer and Daukantaite (2020) reviewed a great deal of empirical evidence supporting the connection between the organismic valuing theory of personal growth and self-transcendence. In a qualitative study of highly self-transcendent individuals, Reischer et al (2021) confirmed that such individuals tended to narrate their lived experiences as spiritual journeys of humanistic growth toward self-transcendence during the later middle age.…”
Section: Self-transcendence As Personal Growthmentioning
confidence: 82%
“…Likewise, Maurer and Daukantaite (2020) reviewed a great deal of empirical evidence supporting the connection between the organismic valuing theory of personal growth and self-transcendence. In a qualitative study of highly self-transcendent individuals, Reischer et al (2021) confirmed that such individuals tended to narrate their lived experiences as spiritual journeys of humanistic growth toward self-transcendence during the later middle age.…”
Section: Self-transcendence As Personal Growthmentioning
confidence: 82%
“…More research is needed to determine whether these themes or others are particularly prominent in older adulthood, and to identify whether established findings in the narrative identity literature replicate or diverge in late life. For example, narrative coding schemes developed for use with midlife adults, including those which measure emotional resolution (Pals, 2006), ego integrity (Torges, Stewart, & Duncan, 2008), and self-transcendence (Reischer, Roth, Villarreal, & McAdams, 2020), could be applied to research with older adults.…”
Section: Salient Narrative Themes In Older Adults' Narrativesmentioning
confidence: 99%
“…More research is needed to determine whether these themes or others are particularly prominent in older adulthood, and to identify whether established findings in the narrative identity literature replicate or diverge in late life. For example, narrative coding schemes developed for use with midlife adults, including those which measure emotional resolution (Pals, 2006), ego integrity (Torges et al., 2008), and self‐transcendence (Reischer et al., 2020), could be applied to research with older adults. The outcome of this research might suggest that the metaphor of a narrative reader, smoothing over and integrating their life story in older adulthood, is quite apt; alternatively, it might undermine or refine this concept in other ways that help to illuminate the interaction between aging and narrative identity.…”
Section: Authoring To Readingmentioning
confidence: 99%
“…We are indebted toReischer et al (2019) for this excellent format for presenting a master narrative prototype. Reischer, H. N., Roth, L. J., Villarreal, J.…”
mentioning
confidence: 99%